Phoenicians at Huelva - Lipiński, Edward (Anabasis. Studia Classica et Orientalia, 2016)
Phoenician presence and activity in the area of Huelva, in the south-western part of the Iberian Peninsula, is attested since the 9th/8th centuries B.C. not only by imported pottery, but also by Phoenician graffiti and ostraca. Judging from palaeography, the oldest inscriptions go back at least to the 8th century B.C. Even a Phoenician altar from that period was found at Riotinto, 50 km north of Huelva. The famous copper mines of this site and of nearby places have attracted the Phoenicians who were extracting silver by cupellation from the amounts of local gossan or argentiferous jarosite. Huelva was the port of shipment of the ores from the Sierra Morena, brought by the Tinto River from the mining area to the harbour.